The Contribution of Film "Upin & Ipin" on Language Development and Psycholinguistic Patterns of Children - Saputra, Nefri Andra (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2018)
One of the children's film series that is very popular with many children now, especially Indonesia, is a film titled "Upin & Upin." The phenomenon that has been seen in recent times is the Upin and Ipin language styles, which tend to be imitated and often spoken by children in Indonesia. This Malay utterance often appears on many occasions. This research was conducted to make an interpretation of the phenomenon that occurs. The phenomenon interpreted in this study is the impact and effect of the film "Upin & Ipin" on children's language development. Special focus is on the differential phase that is generally experienced by children aged three to five years.